Cyclic Voltammetry and RRDE Studies on the Electrochemical Behavior of Azetidinone Ester - Kulandainathan,M. Anbu (2005)
Azetidinone ester is the key intermediate during the synthesis of injectable cephalosporin compounds. This intermediate is undergoing electrochemical reaction during the process of conversion from penicillin to cephalosporin. The CV and RRDE studies clearly indicate that electro-reduction of this compound is taking place in three steps under the condition. The first two peaks correspond to the two, one electron transfers and the third one is due to the proton addition from the non-aqueous solvent. And during the process, the cyclisation is also taking place in order to neutralise the charge. Further CV and RRDE studies with the addition of small amount of water to the above system clearly confirm the mechanism. This was very well confirmed by the FTIR analysis of the product obtained from the bulk electrolysis.